Gender differences in grief narrative construction: a myth or reality?. Issue 1 (31st December 2019) - Stelzer, Eva-Maria; Atkinson, Ciara; O'Connor, Mary-Frances; Croft, Alyssa
ABSTRACT: Background : Narratives play a central role in the recovery process following death, and linguistic properties of grief narratives can serve as indicators of adjustment to loss. The present study examined whether bereaved men and women differ in how they discuss their loss, and how linguistic markers relate to psychological functioning. Positive associations were hypothesized between first-person singular pronoun use and psychological distress. Gender differences were expected for different emotion and social process words, and overall word use. Exploratory analyses were conducted to assess the relationship between linguistic markers and psychosocial outcomes for men and women separately. Method : 50 bereaved widow(er)s and parents (29 women, 21 men; M Age  = 71.16 years, SD  = 9.95) completed psychosocial self-report questionnaires and individual in-depth interviews. Grief narratives were analysed using Linguistic Inquiry and Word Count (LIWC), a software program that quantifies words into linguistic and psychological categories. Results : Contrary to our hypothesis, first-person pronoun use was not related to psychological distress. Although gender differences emerged in self-reported psychosocial outcomes, we failed to find the predicted gender differences in linguistic markers (emotion and social process words, overall word count). Exploratory analyses revealed additional associations between linguistic markers and psychosocial outcomes, and gender differences in these relationships. Notably, first-person pronoun use was related to heightened grief avoidance. Furthermore, various linguistic markers were associated with increased depression levels in females, but not males. In contrast, nonfluencies were positively associated with indicators of psychological distress in men only. Conclusion : In line with the gender similarities hypothesis, analyses suggest similarities between men and women's discussion of their grief experience. Associations between linguistic markers and psychological adjustment indicate that grief narratives contain meaningful indices of underlying health. HIGHLIGHTS: Narratives constitute one way to make sense of loss. The present study investigated linguistic properties of grief narratives, explored gender differences in linguistic markers, and their relationship to mental health. Associations between linguistic markers and psychological adjustment indicate that grief narratives contain meaningful indices of underlying health. For instance, first-person pronoun use was positively associated with grief avoidance. Men and women are more similar than different in discussing loss, despite self-reported differences in adjustment.